Transcriptome Analyses of Senecavirus A-Infected PK-15 Cells: RIG-I and IRF7 Are the Important Factors in Inducing Type III Interferons - Peng, Kenan; Deng, Lishuang; Wei, Jianfeng; Zhao, Jun; Deng, Huidan; Tao, Qian; Jiang, Chaoyuan; Zeng, Yubing; Li, Fei; Zhang, Rubo; Sun, Xiangang; Xu, Zhiwen; et al. (Frontiers in Microbiology, 2022)
Senecavirus A (SVA) is a new type of virus related to swine vesicular disease, which results in enormous economic losses worldwide. At present, the host transcriptional responses to SVA infection, host-SVA interactions, and the mechanism of SVA in innate immune modulation are not well understood. This study explores the gene expression profiles of PK-15 cells at 0, 6, 12, 18, 24, 36 h SVA post-infection by RNA sequencing. Our analysis identified 61, 510, 1,584, 2,460, and 2,359 differentially expressed genes (DEGs) in the comparison groups S6 vs. Control, S12 vs. Control, S18 vs. Control, S24 vs. Control, S36 vs. Control, respectively. The reproducibility and repeatability of the results were validated by RT-qPCR, and all DEGs exhibited expression patterns consistent with the RNA-seq results. According to GO enrichment analysis and KEGG pathway analysis of DEGs in different periods after SVA infection, we found that SVA infection significantly modified the host cell gene-expression patterns and the host cells responded in highly specific manners, including response to signal reception and transmission, external biotic stimulus, response to the virus and host immune defense response. Notably, we observed the specific induction of type III interferon IFN-λ1 and IFN-λ3, which indicated that type III interferon plays an important antiviral function in PK-15 cells. Furthermore, our results showed that SVA might be recognized by RIG-I/MDA-5 receptors first after infecting PK-15 cells and then activates downstream IRF7-mediated signaling pathways, causing an increase in the expression of type III interferon. This study could provide important insights into the modulation of host metabolism during SVA infection and provide a strong theoretical basis for a better understanding of the pathogenic mechanism and immune escape mechanism of SVA.